(untitled) (Mongolian Journal of Applied Linguistics, 2024)
In his previous research, the author concluded that the Modern Mongolian Standard Dialect, or Khalkha-based literary language, has already developed the category of “Unpleasantness.” The tendency to express unpleasant actions is not a new feature in the Mongolian language. Nicolas Poppe correctly noted that the passive structure in the Secret History of the Mongols is used for actions that either indirectly affect the subject or are performed against the subject’s will. In Classical Mongolian Literary Language, there are two different verb derivational suffixes: -D and -Da/De. Both suffixes derive verbs from adjectives, but with a key distinction: verbs formed with -D indicate regular actions, whereas verbs formed with -Da/De convey unpleasant actions. For example, qolad- means simply “to become or to get farther,” while qolada- means “to become too far” or “to become unpleasant due to excessive distance.” The Modern Mongolian Standard Dialect tense system clearly distinguishes between unpleasant actions. The past tense negative -сангүй, present continuous -аад байна, and present continuous negative -хгүй байна all indicate unpleasant actions. In this paper, the author demonstrates that the Modern Mongolian Myangad dialect uses the verb structure “Es Verb stem + juu” to express unpleasant actions. This suggests that the category of “Unpleasantness” might be a universal feature across all Mongolian dialects. Мянгад аялгууны “Эс үйл + жуу/жүү” бүтцийн хэл зүй, утга зүйн онцлог Хураангуй: Орчин цагийн утга зохиолын монгол хэл буюу халх суурьтай баримжаа аялгууны цаг заах тогтолцоонд үйлийн зохистой ба зохисгүйг ялган заах хандлага төдий бус, тусгай ай нэгэнт үүсэн бий болжээ. Өнгөрсөн цагийн үгүйсгэх “-сангүй”, үргэлжилж буй одоо цагийн “-аад байна”, үргэлжилж буй одоо цагийн үгүйсгэх “-хгүй байна” хэлбэрүүд бүгд тухайн үйлийн зохисгүйг заах утгаараа нэгдмэл юм. Зохисгүй утга заах тусгай хэлбэр нь монгол хэлнээ цоо шинэ зүйл биш, Монголын нууц товчоон дахь үйлдэгдэх хэвийн хэрэглээ нь үйлийн эзнээс хамааралгүй болсон, хэцүү таагүй үйлд өртсөн утгыг илэрхийлдэг байв. Монгол бичгийн хэлний тэмдэг нэрээс үйл үг бүтээх -д болон -да/дэ дагаврын ялгаа ч мөн зохисгүй хэмээх утга мөн. Энэхүү өгүүлэлд орчин цагийн мянгад аялгууны “Эс үйл үг + жуу” бүтцийг судалж, зохисгүй утга илтгэх тусгай хэлбэр болохыг нь батлах юм. Тэгэхлээр ерөөс үйлийн зохистой зохисгүйг ялган заах нь монгол хэлний төв аялгуу төдий бус нийт монгол хэл аялгуудын универсал шинжтэй үзэгдэл байж болох юм. Түлхүүр үг: Мянгад аялгуу, хэл зүйн ай, зохистой зохисгүйн ай, зохисгүй утга